Accessing care coordination information: the non-statutory sector contribution. (12th December 2016) - Jasper, Rowan; Hughes, Jane; Sutcliffe, Caroline; Abendstern, Michele; Loynes, Niklas; Challis, David
Abstract : Purpose: The provision of information and advice for older people arranging their own care is a policy objective. The purpose of this paper is to explore the range and scope of web-based information about care coordination activities for older people in the non-statutory sector in England. Design/methodology/approach: Non-statutory organisations were identified through a structured internet search. Services were screened to identify those providing at least one care coordination activity. A postal survey of services was conducted in 2014 and results compared with the initial findings of the web search. Findings: Almost 300 services were identified, most of which were provided by three organisations: Age UK; Alzheimer's Society; and the British Red Cross. Brokerage was the most frequently reported care coordination activity; the majority of services focussed on help to stay at home; and carers and older people (including those with dementia) were the target groups most often identified. Comparison of the two information sources revealed a significant agreement between two care coordination's activities: compiling support plans and monitoring and review. Research limitations/implications: Findings are based on a purposive sample of organisations and therefore care must be exercised in generalising from them. Originality/value: This study is one of the first to systematically explore the nature and extent of information about care coordination activities provided by the non-statutory sector in England. It was conducted when policy advocated both an increased role for the non-statutory sector and an increase in self-directed support.